PEMANFAATAN APLIKASI KINEMASTER SEBAGAI MEDIA PEMBELAJARAN IPS KELAS 1V SDN TANJUNG BARULAK PADA MASA COVID 19 - Depi Putri Afriyenti; Adam Mudinillah (LPPM STAI Muhammadiyah Probolinggo, 2021)
Based on research on the use of the kinemaster application as a social science learning medium for class 1V SDN Tanjung Barulak, Batipuh District, Tanah Datar Regency, during the covid 19 period. This disease can be transmitted anywhere, for example, people holding objects that are held by the person can also be transmitted if we meet face to face with the covid. In the world of education in terms of benefits. The COVID-19 pandemic has caused a lot of anxiety in a negative way for the community. By learning during the pandemic, students and college students take part in learning with the kinemaster application that is currently taking place. Learning is carried out online or online during online learning, students learn by using smartphones, laptops or other applications, learning during this pandemic will not be effective and conducive. The use of kinemaster videos can also increase students' attention, thus making the online learning atmosphere fun and interesting for students without causing difficulties for students. And the number of students who experience complaints in this online learning. Therefore, we have to be patient even though something happens to all Indonesian citizens who experience difficulties in terms of learning.